Pays, mouvements et sons dans la vallée de Grande-Rivière : pour une approche phénoménologique des paysages de Guadeloupe - Catherine Benoît (VertigO, 2012)
There is no doubt for an European gaze that Caribbean nature can be perceived as made of andscapes, but is it the same for the people of Guadeloupe? If we define landscape as the cultural expression, driven by the sight, of the relationship that an individual or social group has with its own environment, then this concept does not reflect the primary relationship that Guadeloupeans have of their environment. The analysis of the perception and the experience that the people of the Grande-Rivière valley has of its environment actually shows the existence of a multisensory aesthetic that favors hearing, the sense of movement and well-being in assessing a place. This article proposes a phenomenology of landscape in the 1990s’ before the development of landscape public policy planning that may have changed the experience of the environment.